Morfologi Biji Indigofera sebagai Karakter Penciri dalam Studi Taksonomi - Muzzazinah, Muzzazinah (Bioedukasi: Jurnal Pendidikan Biologi, 2020)
Characteristics of seeds such as seed shape, color, size, texture of the seed coats and  hilum shape can be used to solve classification problems. With biology microskop  observations obtained under specification of character seeds for 12 species of  Indigofera  from Indonesia and Saudi Arabia. The results showed that the pattern of seed coat ornamentation, hilum, seed shape may help in the identification of the species..